Evaluation of the rectal‐interdigital temperature gradient as a diagnostic marker of shock in dogs. Issue 6 (23rd September 2020) - Schaefer, Jonathan D.; Reminga, Christin L.; Reineke, Erica L.; Drobatz, Kenneth J.
Abstract: Objective: To evaluate the difference in the rectal‐interdigital temperature gradient (RITG) between dogs that were presented to an emergency room with clinical signs of shock compared to those without signs of shock, and if this gradient can be used as a diagnostic marker for shock. Design: Prospective, single center, observational study conducted from 2014 to 2015. Setting: University veterinary teaching hospital. Animals: Twenty dogs with a clinical diagnosis of shock and 60 dogs without a clinical diagnosis of shock (controls). Measurements and main results: Upon presentation to the emergency room and prior to intervention, measurements of rectal temperature, interdigital temperature, ambient temperature, systemic markers of perfusion (capillary refill time [CRT], heart rate [HR], respiratory rate [RR], Doppler blood pressure [DBP], and venous plasma lactate concentration), and venous blood gas analytes were recorded. Dogs were initially determined to be in shock by the attending clinician, and post hoc inclusion criteria were applied. Shock was defined as abnormalities in ≥3 of the 6 following criteria: HR > 120/min, RR > 40/min, CRT > 2 seconds, rectal temperature <37.8°C (100.0°F), venous plasma lactate concentration >2.5 mmol/L, or DBP < 90 mm Hg. Animals with circulatory shock had a significantly increased RITG. An increased RITG was also correlated with individual perfusion parameters including prolonged CRT ( ρ = .353, P  = 0.0013), tachycardia ( ρ = .3485, P  = 0.0015), decreased DBP ( ρ = –0.6162, P  = 0.0003), and shock index ( ρ = 0.6168, P  = 0.0003). Receiver operator curve analysis indicated a RITG cutoff point of 11.6°F had 90% specificity for the diagnosis of shock (area under the curve = 0.7604). Conclusions: The RITG in this study was associated with a diagnosis of shock and therefore may serve as a diagnostic marker of circulatory shock. Future studies with larger sample sizes to validate the use of temperature gradients and other peripheral perfusion abnormalities as diagnostic and monitoring tools are warranted.